Unique pathological features and drug resistance patterns in cutaneous tuberculosis - Liu, Yuejiao; Wu, Runrui; Liu, Junjun; Dai, Jinlong; Liu, Dongxu; Liu, Yadong; Liang, Yumei; Chen, Wen (Frontiers in Microbiology, 2025)
Cutaneous tuberculosis (CTB), a rare manifestation of extrapulmonary tuberculosis, often presents diagnostic challenges in clinical settings due to its atypical presentation. The definitive diagnosis relies heavily on pathological evaluation, which underscores the importance of understanding the distinct pathological characteristics and drug resistance patterns of CTB, a subject that has not been extensively explored previously. In this study, we conducted a comparative analysis of 59 CTB samples and 59 pulmonary tuberculosis samples, focusing on their clinicopathological features. Our findings reveal that CTB can be characterized by subcutaneous irregular hypoechoic regions on ultrasound, localized soft tissue swelling, and flaky low-density shadows on CT scans, with MRI effectively determining the extent of bone and soft tissue involvement. The two groups had no statistical difference in the positivity rate for acid-fast staining and molecular detection. Notably, the incidence of granulomatous lesions was higher in CTB compared to pulmonary tuberculosis, and the high number of macrophages in the skin may be an important reason. However, other parameters such as caseous necrosis, coagulative necrosis, inflammatory necrosis, acute inflammation, hemorrhage, fibroplasia, and exudation showed no significant differences between the two groups. Intriguingly, many significant differences in drug resistance patterns were found between the CTB group and the control group. But when comparing the secondary CTB group to the control group, the only significant difference found was in resistance to RFP + INH + STR. Overall, our study highlights unique pathological features and drug resistance profiles in CTB, providing valuable insights for more accurate clinical diagnosis and tailored therapeutic strategies.